Gender Bias in Quranic Interpretation: An Epistemological Analysis of the Role of Interpreters and Social Structure - Pandy Pratama; Ranjan Owen; Samia Woodring; Emilie Abraham; Emily Gupta (Arba: Jurnal Studi Keislaman, 2026)
Studies of Quranic interpretation have often reproduced hierarchical and androcentric interpretations of gender relations, particularly in the classical and some modern traditions, without adequate analysis of the epistemological framework, the interpreter’s subject position, and the social structures surrounding the production of meaning. This gap demonstrates the limitations of the textual-normative approach, which tends to ignore the epistemological dimension of knowledge and power relations in the interpretive process. This study aims to critically analyze the sources, mechanisms, and patterns of gender bias in Quranic interpretation by examining the relationship among the epistemology of interpretation, the interpreter’s subjectivity as an epistemic subject, and the patriarchal social structures that influence interpretive practices. This study uses a qualitative method grounded in literature reviews of representative feminist works, employing an epistemological-critical analysis to examine the assumptions underlying knowledge, scientific authority, and methodological legitimacy. The results of this study indicate that gender bias in interpretation does not originate from the Quranic text itself, but rather is a construction of knowledge shaped by androcentric epistemological assumptions, the interpreter’s historical experience and social position, and patriarchal power relations that construct interpretive authority. These findings also reveal that the choice of interpretive methods, the hierarchy of scholarly authority, and the naturalization of certain interpretive traditions all play a significant role in systematically reproducing gender bias. This study concludes that deconstructing gender bias in interpretation requires an interpretive epistemological framework that is reflective, contextual, and sensitive to gender justice as an important implication for the development of contemporary critical interpretation studies.